PENDETEKSIAN RESIKO AUTIS PADA ANAK MENGGUNAKAN PEMETAAN M-CHAT-R - Mardiah Mardiah; Musdalina Musdalina (Jurnal Ilmiah Kebidanan Imelda, 2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by difficulties in social interaction, communication, and behavior. Early detection of ASD is important for appropriate intervention. This study aims to detect the risk of autism in children aged 16-30 months in Langkat Regency using the M-CHAT-R (Modified Checklist for Autism in Toddlers-Revised) instrument. Methods: This study is a cross-sectional study conducted on 50 children aged 16-30 months who were screened using M-CHAT-R. The analysis was performed using chi-square and Fisher's tests to examine the relationship between gender, premature birth, low birth weight (LBW), family history of autism, and seizure history (epilepsy) with ASD risk. Results: The results showed that male gender was a significant risk factor for ASD (P<0.001). Other factors such as family history of autism, LBW, and seizure history did not show a significant association with ASD (P>0.05). A total of 10% of the children had LBW, and 6% were born prematurely. Conclusion: Male gender is a significant risk factor for ASD, with boys being 1.4 times more at risk compared to girls. Furthermore, no significant correlation was found between family history of autism, LBW, premature birth, or seizure history with ASD. Further research is needed to explore the genetic and environmental factors contributing to ASD in Indonesia.